Measurement of absolute and relative reliability during the countermovement and split-squat jump using PUSH Pro Band 2.0. - McCurdy, K.; Walker, J.; Pozuc, D.; Pitts, J. (International Journal of Strength and Conditioning, 2022)
The purpose of this study was to determine the relative and absolute reliability using PUSH Pro Band 2.0 IMU to measure peak velocity and power during the countermovement (CMJ) and split-squat jump (SSJ). Twenty-three resistance trained males and females completed the study. After a familiarization session, each subject completed 2 identical sessions separated by a minimum of 72 hours that included 4 loads during the CMJ (body weight, body weight plus 20, 40 and 60%) and SSJ (body weight, body weight plus 15, 30 and 45%). In each session, 3 repetitions were completed at each load in randomized order with 3 minutes rest between sets and 5 minutes rest between jump types. Dumbbells held to the side were used to add load. A waist belt was worn that contained the accelerometer. High relative (intra-class coefficient ranging from 0.86-0.99) and absolute (coefficient of variation ranging from 1.7-8.0%) reliability were found for all measures of peak velocity and power during the CMJ and SSJ. The PUSH device produced highly reliable measures of jump performance across all loads between trials and across sessions.